2008
DOI: 10.1016/j.jacl.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols and stanols: Their role in health and disease

Abstract: Mammalian physiological processes, and likely any organism with a biliary tree, can distinguish between dietary cholesterol and non-cholesterols, retaining very little of the non-cholesterol in their bodies. Historically, the distinction between plant sterols and cholesterol has been known about for a century or more. That plants sterols were not 'absorbed' has been investigated for almost half a century. Indeed, the oral of plant sterols in gram quantities was shown to interfere with cholesterol absorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 59 publications
1
25
0
3
Order By: Relevance
“…1 Although 20% to 80% of dietary cholesterol is absorbed, 2 dietary plant sterols, which include stigmasterol, campesterol, and sitosterol, are normally actively excreted, resulting in less than 1% retention. 3 Clues that a specific molecular mechanism was involved in the selective removal of phytosterols were first provided by Bhattacharyya and Conner in a 1974 description of extensive tendon xanthomas and unusually high levels of b-sitosterol with normal cholesterol levels in 2 sisters suffering from what is now most commonly known as sitosterolemia.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although 20% to 80% of dietary cholesterol is absorbed, 2 dietary plant sterols, which include stigmasterol, campesterol, and sitosterol, are normally actively excreted, resulting in less than 1% retention. 3 Clues that a specific molecular mechanism was involved in the selective removal of phytosterols were first provided by Bhattacharyya and Conner in a 1974 description of extensive tendon xanthomas and unusually high levels of b-sitosterol with normal cholesterol levels in 2 sisters suffering from what is now most commonly known as sitosterolemia.…”
Section: Introductionmentioning
confidence: 99%
“…2 g per day associated with reduction in cholesterol absorption with effects on membrane cholesterol molecular mechanisms [97][98][99].…”
Section: Phytosterols and Cholesterol Homeostasismentioning
confidence: 99%
“…Brain cholesterol homeostasis and phytosterol intake are closely interlinked and diets with specific composition of phytosterols are possibly important in the maintenance of liver, brain and oxysterol metabolism [97][98][99][100][101][102][103][104][105][106]. Phytosterols such as campesterol and stigmasterol inhibit intestinal cholesterol absorption and beta-sitosterol and stigmasterol act on the liver to reduce cholesterol levels (Figure 2, ref [97,99,101]).…”
Section: Phytosterols and Cholesterol Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…PS lowers plasma cholesterol by 10-15% when the PS intake is 0. .0 g/day (9). Several trials have shown that 2 g/day of phytostanols can lower plasma lowdensity lipoprotein (LDL)-cholesterol (LDL-C) from 9 to 14% (6).…”
Section: Introductionmentioning
confidence: 99%